Implementation of DSN-MUI Fatwa No. 108/DSN-MUI|X|2016 in The Development of Halal Tourist Destinations in The City of Cirebon: The Perspective of Maqashid Syariah - Al Mustaqim, Dede (International Journal of Social and Management Studies, 2023)
This study aims to analyze the implementation of the DSN-MUI Fatwa No. 108/DSN-MUI|X|2016 in the development of halal tourist destinations in Cirebon City with the Maqashid Syariah perspective. Research using qualitative methods. Through this research, it was found that the implementation of the DSN-MUI Fatwa No. 108/DSN-MUI|X|2016 has had a positive impact on the development of halal tourist destinations in the city of Cirebon. Development of halal tourism infrastructure, provision of halal accommodation, halal restaurants and culinary, halal activities and recreation, as well as marketing and promotion of halal tourism, have experienced significant developments. This implementation has met the needs of Muslim tourists, increased the attractiveness of the City of Cirebon as a halal tourist destination, and contributed to the economic and social development of the City of Cirebon. In the context of Maqashid Syariah’s perspective, the application of halal tourism destinations in Cirebon City has succeeded in meeting primordial needs (Hifz al-Din, Hifz al-Nafs), rational needs (Hifz al-Aql), and moral and ethical needs (Hifz al-Nasl, Hifz al-Mal).